Prevalence of endemic pig-associated zoonoses in Southeast Asia: A review of findings from the Lao People's Democratic Republic - Okello, A.L.; Burniston, S.; Conlan, J.V.; Inthavong, Phouth; Khamlome, Boualam; Welburn, S.C.; Gilbert, Jeffrey; Allen, J.; Blacksell, Stuart D. (American Society of Tropical Medicine and Hygiene, 2015)
The increasing intensification of pork production in southeast Asia necessitates an urgent requirement to better understand the dual impact of pig-associated zoonotic disease on both pig production and human health in the region. Sharing porous borders with five countries and representing many regional ethnicities and agricultural practices, Lao People's Democratic Republic (Lao PDR) appears well placed to gauge the levels of pig-associated zoonoses circulating in the wider region. Despite this, little is known about the true impact of zoonotic pathogens such as leptospirosis, Trichinella, hepatitis E virus (HEV), Japanese encephalitis (JE), and Taenia solium on human health and livestock production in the country. A comprehensive review of the published prevalences of these five pig-associated zoonoses in Lao PDR has demonstrated that although suspicion remains high of their existence in pig reservoirs across the country, epidemiological data are scarce; only 31 epidemiological studies have been undertaken on these diseases in the past 25 years. A greater understanding of the zoonoses prevalence and subsequent risks associated with pork production in the southeast Asian region could help focus public health and food safety interventions at key points along the value chain, benefiting both livestock producers and the broader animal and human health systems in the region.